Nitrogen Supply Mitigates Temperature Stress Effects on Rice Photosynthetic Nitrogen Use Efficiency and Water Relations - Zhuang Xiong; Fangzhou Zheng; Chao Wu; Hui Tang; Dongliang Xiong; Kehui Cui; Shaobing Peng; Jianliang Huang (Plants)
Climate-change-induced temperature fluctuations pose significant threats to global rice production, particularly through their impact on photosynthetic efficiency. The differential mechanisms by which low and high temperatures affect leaf photosynthetic processes in rice remain poorly understood. Here, we investigate the effects of temperature stress (15 °C, 30 °C, 45 °C) on rice photosynthetic performance across a gradient of nitrogen supply levels: low nitrogen (LN), medium nitrogen (MN), and high nitrogen (HN). The low temperature exhibited stronger negative impacts on photosynthesis than the high temperature, primarily through increased mesophyll limitation and disrupted cellular CO2 diffusion, while the high temperature showed less pronounced effects, particularly under HN and MN conditions. While photosynthetic nitrogen use efficiency (PNUE) decreased with increasing nitrogen under the optimal temperature, moderate nitrogen supply maintained optimal PNUE under temperature stress, suggesting that a balanced nitrogen level is crucial for maximizing both photosynthetic capacity and nitrogen use efficiency. Plants with adequate nitrogen maintained higher intrinsic water use efficiency (iWUE) under both temperature extremes through improved coordination between CO2 uptake and water loss. Our findings reveal distinct mechanisms underlying low- and high-temperature stress effects on photosynthesis and highlight the importance of optimizing nitrogen management for enhancing crop resilience to temperature extremes under climate change.